Integrating think-pair-share and mind mapping as an effective strategy to develop response text writing skills - Lina Siti Nurwahidah; Afni Falah; Winka Naida; Ari Kartini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
The low skill in writing response texts among junior high school students is often caused by limited enthusiasm and difficulty in organizing ideas systematically. This study aims to examine the effectiveness of the Think-Pair-Share model, assisted by mind mapping, in improving response-text writing skills and to identify students' perceptions and the challenges teachers face during its implementation. The research employed a quantitative, pre-experimental design with a one-group pretest–posttest. The sample consisted of 30 seventh-grade students at SMP Asshidiqiyah in Garut Regency, Academic Year 2024/2025, selected via cluster random sampling. Data were collected through tests, questionnaires, and interviews, and analyzed using the Wilcoxon test and normalized gain calculations with SPSS version 25.0. The results indicate that the Think-Pair-Share model with mind mapping effectively enhanced students' writing skills, as evidenced by an Asymp. Sig. (2-tailed) value of 0.000 < 0.05 and an average normalized gain of 73.33%, which falls into the medium category. Furthermore, 75.3% of students responded positively to the use of the model and media, while technical and classroom management obstacles were successfully addressed through appropriate instructional strategies. It is concluded that the Think-Pair-Share model, supported by mind mapping, is recommended as an alternative for Indonesian language instruction, particularly for teaching narrative-genre text writing.